Case report: A case of incontinentia pigmenti - Lingfeng Xie; Lingfeng Xie; Yong Zhu; Liya He; Bing Yu; Jiajue Wang; Ruiqiang Fan; Xiumei Mo; Xiumei Mo; Yu Zhang; Ting Xie; Ting Xie (Frontiers in Medicine, 2023)
Incontinentia pigmenti (IP) is a rare neuroectodermal dysplasia caused by mutations in the IKBKG gene. We present a case of a 4-month-old female infant with erythematous vesicular skin lesions on the trunk and extremities. Histopathologic examination of the blisters revealed an eosinophilic infiltrate. Further investigation revealed that her mother had three unexplained miscarriages and two normal uncomplicated pregnancies, resulting in the birth of two male infants. We performed a comprehensive genetic evaluation to rule out the interference of pseudogene IKBKGP, and the infant was finally diagnosed with IP. During the subsequent 2-year follow-up, we observed a significant improvement in her dermatologic symptoms, with no evidence of recurrence, and there were no other associated symptoms in the hair, nails, oral mucosa, eyes, or central nervous system.